Beyond the Stereotypes: Unveiling Signs in “Flip the Script” Video Champaign for Sustainable Development Goals - Dewi, Ni Made Sinta; Juniartha, I Wayan (Humanis; Vol 28 No 2 (2024)DO - 10.24843/JH.2024.v28.i02.p09, 2024)
This study employs semiotic analysis to examine the verbal and visual signs within the "Flip the Script" video campaign and explore their interplay in conveying the campaign's intended message. Additionally, the research categorizes the United Nations Sustainable Development Goals (SDGs) depicted in the campaign, drawing from Chandler's (2007) and Leech's (1981) theories The findings highlight the presence of connotative meanings that significantly enhance communication strategies. Through linguistic and visual exploration, the study analyzes how signs and metaphor-driven words resonate deeply with viewers. The process of categorizing SDGs bolsters the campaign's mission of advancing sustainable development, harnessing semiotics to foster nuanced comprehension and forge meaningful connections. The findings of the study shed light on how the campaign video effectively confronts stereotypes and disrupts ingrained societal biases by presenting diverse narratives. This contribution ignites inclusive dialogues and steers positive transformation, enhancing the understanding of the campaign's impact on societal perceptions and behaviors.